2012
DOI: 10.1590/s0102-79722012000300015
|View full text |Cite
|
Sign up to set email alerts
|

Imagem corporal e hábitos alimentares na anorexia nervosa: uma revisão integrativa da literatura

Abstract: ResumoRevisão integrativa da literatura com objetivo de investigar os construtos da imagem corporal e hábitos alimentares na anorexia nervosa (AN). As bases consultadas foram MedLine, LILACS e PsycINFO, no período de 2005 a 2009. A maioria dos artigos encontrados é constituída de estudos não-experimentais e descritivos, provenientes de fontes internacionais. Os resultados evidenciaram que a personalidade de mulheres com AN é permeada por baixa autoestima, sentimentos de inferioridade, inadequação, insegurança,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
10

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
0
3
0
10
Order By: Relevance
“…This was shown in a study with 471 adolescents, which identified 62.8% with low self-esteem, 23.2% preoccupied with body image, and 21.7% with risky eating behavior for developing eating disorders. (16,17) In the sample, 45.8% of the students presented some preoccupation with body image. These findings are similar, with the results of 47% of 300 students of a nutrition course in Brazil; they are higher than the result of a study conducted in Juiz No significant difference was identified between the scores on the instrument and the risk classification between the classes, but a simple positive correlation was found between the EAT and BSQ instruments (p<0.001), that is, the risk for eating behavior was present in 20 (66.7%) students of the 30 (100%) who presented risky eating behavior ( Table 1).…”
Section: Discussionmentioning
confidence: 96%
“…This was shown in a study with 471 adolescents, which identified 62.8% with low self-esteem, 23.2% preoccupied with body image, and 21.7% with risky eating behavior for developing eating disorders. (16,17) In the sample, 45.8% of the students presented some preoccupation with body image. These findings are similar, with the results of 47% of 300 students of a nutrition course in Brazil; they are higher than the result of a study conducted in Juiz No significant difference was identified between the scores on the instrument and the risk classification between the classes, but a simple positive correlation was found between the EAT and BSQ instruments (p<0.001), that is, the risk for eating behavior was present in 20 (66.7%) students of the 30 (100%) who presented risky eating behavior ( Table 1).…”
Section: Discussionmentioning
confidence: 96%
“…The fact that the person with AN has difficulties in facing and positively incorporating the physical and psychological changes that begin in adolescence appears as a recurring pattern in the literature (Bruch, 1973;Leonidas & Santos, 2012;Scorsolini-Comin & Santos, 2012). In the omnipotent attempt to halt the process of growth and differentiation in relation to the maternal body, the person would seek refuge in a squalid, emaciated body, which dramatically expresses their impossibility to enter adulthood (Gaspar, 2005).…”
Section: I'm Not Satisfied You Know But I Will Not Lie When I Saw mentioning
confidence: 99%
“…A literatura específica acerca dos TAs engloba uma quantidade significativa de estudos que apontam para a rede social familiar como a principal fonte de apoio à pessoa acometida (Dimitropoulos, Carter, Schachter, & Woodside, 2008;Kluck, 2008;Leonidas & Santos, 2012;Leonidas, Crepaldi, & Santos, 2013;Limbert, 2010;Marcos & Cantero, 2009;Souza & Santos, 2009, 2010. Marcos e Cantero (2009) destacam que, dentre os membros da família, a mãe e o cônjuge são considerados as principais fontes de apoio social de mulheres com TAs, e essas mulheres admitem estar satisfeitas com o apoio recebido da rede familiar.…”
Section: Transtornos Alimentares E Rede Social De Apoiounclassified
“…Esse desconhecimento alimenta a incompreensão por parte de familiares, professores e colegas de trabalho, incrementando o isolamento social e o sentimento de desamparo e menosvalia da pessoa acometida (Scorsolini-Comin, . Em decorrência disso, o profissional de saúde deve investigar de modo pormenorizado as dimensões constitutivas da rede social de apoio das pacientes, de modo a assegurar o adequado estabelecimento do plano terapêutico individual (Filho & Nóbrega, 2004;Leonidas, & Santos, 2012;Resende, Bones, Souza, & Guimarães, 2006).…”
Section: Transtornos Alimentares E Rede Social De Apoiounclassified